2011
DOI: 10.1029/2011gb004150
|View full text |Cite
|
Sign up to set email alerts
|

Redefinition and global estimation of basal ecosystem respiration rate

Abstract: [1] Basal ecosystem respiration rate (BR), the ecosystem respiration rate at a given temperature, is a common and important parameter in empirical models for quantifying ecosystem respiration (ER) globally. Numerous studies have indicated that BR varies in space. However, many empirical ER models still use a global constant BR largely due to the lack of a functional description for BR. In this study, we redefined BR to be ecosystem respiration rate at the mean annual temperature. To test the validity of this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 123 publications
(100 reference statements)
4
49
0
1
Order By: Relevance
“…6b). Previous studies also indicated that reference respiration depends strongly on mean annual GPP (e.g., Yuan et al, 2011), and can be estimated by LAI max (e.g., Migliavacca et al, 2011) or mean annual springtime EVI (e.g., Jägermeyr et al, 2014).…”
Section: Characteristics Of the Model Parametersmentioning
confidence: 99%
“…6b). Previous studies also indicated that reference respiration depends strongly on mean annual GPP (e.g., Yuan et al, 2011), and can be estimated by LAI max (e.g., Migliavacca et al, 2011) or mean annual springtime EVI (e.g., Jägermeyr et al, 2014).…”
Section: Characteristics Of the Model Parametersmentioning
confidence: 99%
“…For the spatial variability of RE (Reref ), even though it has been gradually confirmed to vary systematically with the spatial variation of productivity (GPP or LAI) and temperature [8,[20][21][22]27,50], to our knowledge, this process has not yet been linked to moisture change in satellite-based RE studies at large scales and with a high resolution. Our findings reveal that Reref has a significant linear relation with LSWI mean in both the Tibetan and Inner Mongolian grasslands (Figure 3, p < 0.01), which is also supported by another recent study in northern China [24].…”
Section: Model Evaluationmentioning
confidence: 99%
“…It is used to describe the difference in basal respiration between sites and years, thereby reflecting the spatial variability of RE [8]. Numerous studies have indicated that a spatially heterogeneous Reref results in a better estimation of RE at different sites [20][21][22]27].…”
Section: Representation Of Spatial Variability Of Rementioning
confidence: 99%
See 2 more Smart Citations